Autologous cord blood mononuclear cell infusion for the prevention of bronchopulmonary dysplasia in very preterm monozygotic twins: A study protocol for a randomized, placebo-controlled, double-blinded multicenter trial - Ren Zhuxiao; Huang Ruoyu; Yang Liling; Ren Xuejun; Yang Chunhui; Ruan Wanfen; Chen Zhifeng; Dai Yiheng; Zhang Qi; Wei Wei; Liu Zhipeng; Pei Jingjun; et al. (Frontiers Media S.A., 2022)
BackgroundPreterm-associated complications remain the main cause of neonatal death. Survivors face the challenges of short- and long-term complications. Among all complications, bronchopulmonary dysplasia (BPD) remains the first important cause of neonatal mortality and morbidity. Current treatment does not address this main preterm complication. Cord blood is regarded as a convenient source of stem cells. The paracrine bioactive factors of stem cells contribute to tissue repair and immune modulation. Our clinical studies and those of others have shown that cord blood cell infusion is both safe and possibly effective in the prevention and treatment of BPD. The therapeutic use of cord blood has emerged as a promising therapy. However, the genetic heterogeneity between control and intervention groups may reduce the comparability especially among small sample trials. The purpose of this study protocol is to investigate the effects of autologous cord blood mononuclear cell (ACBMNC) infusion on the prevention of BPD in very preterm monozygotic twins of less than 32 gestation weeks.MethodsIn this prospective, randomized, placebo-controlled, double-blinded multicenter clinical trial, 60 pairs of monozygotic twin preterm neonates of less than 32 weeks admitted to the Neonatal Intensive Care Unit are randomly assigned to receive intravenous ACBMNC infusion (targeted at 5 × 107 cells/kg) or placebo (normal saline) within 24 h after birth in a 1:1 ratio. The primary outcome will be survival without BPD at 36 weeks of postmenstrual age. The secondary outcomes will include the mortality rate, BPD severity, other common preterm complication rates, respiratory support duration, length and cost of hospitalization, and long-term respiratory and neurodevelopmental outcomes during a 2-year follow-up. Furthermore, we will perform single-cell RNA sequencing for cord blood cells and blood cells 3-10 days after intervention and detect whether reactive oxygen species and inflammatory cytokines are present.ConclusionThis will be the first randomized, placebo-controlled, double-blinded trial to evaluate the efficacy of ACBMNC infusion to prevent BPD in monozygotic twin premature infants and investigate the underlying protective mechanisms. The results of this trial will provide valuable clinical evidence for translational application of cord blood cell therapy in very preterm infants.Trial registration: ClinicalTrials.gov, NCT05087498, registered 10/09/2021, https://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid=S000BAD7&selectaction=Edit&uid=U0002PLA&ts=2&cx=qvyylv.